A censura ao jornal O São Paulo durante a ditadura militar (1964-1985): desafio à evangelização na cidade de São Paulo - Braga, Luiz Claudio de Almeida (2010)
The Roman Catholic Church is not only a message of salvation: it is the message itself. It is a sign of Christ's presence on earth. Currently the Church is called to be the signal through the media: radio, TV, internet and newspaper. Since 1956, the Archdiocese of St. Paul owns the newspaper the São Paulo, which aims to answer the call of this advertisement through social media. Throughout its history this weekly even fought for an end to military dictatorship and its pages had been mutilated by the censorship of the federal government. After 54 years of its creation, after a month of struggles for social justice law and the newspaper still plays its role in society, but with far less visibility and expression. This research aims at performing a radiograph of the newsletter of the Archdiocese of St. Paul, and whether, 54 years after its creation, and 14 years after his censure, this weekly is still providing good role to be those who have no voice voice in society, and to dialogue with the postmodern world around them